2008
DOI: 10.2217/14796678.4.4.373
|View full text |Cite
|
Sign up to set email alerts
|

New Concepts in Transcatheter Closure of Paravalvular Leaks

Abstract: New catheter techniques and a large variety of endovascular devices permit transcatheter treatment - not only of common atrial or ventricular septal defects - but also of rare intracardiac malformations such as postmyocardial infarction ventricular septal defects, sinus valsalva aneurysm or paravalvular leak. Owing to the variable anatomical nature of paravalvular leaks, closure may be one of the most challenging interventional procedures in the field of structural heart disease. Current literature documents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…In this study, patients demonstrated significant and marked improvement in Procedure-related death 1 (2) both CHF symptoms and the need for blood transfusions for ongoing hemolysis. Hein et al (18) observed that 33% of patients requiring transfusions had worsening hemolysis after the procedure, and there was newly developed hemolysis in 10% of all patients. This series had similar results immediately after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, patients demonstrated significant and marked improvement in Procedure-related death 1 (2) both CHF symptoms and the need for blood transfusions for ongoing hemolysis. Hein et al (18) observed that 33% of patients requiring transfusions had worsening hemolysis after the procedure, and there was newly developed hemolysis in 10% of all patients. This series had similar results immediately after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Technical difficulties include crossing the leak, stable device delivery and interference with surrounding structures (particularly valve leaflet impingement and coronary ostia obstruction) [1,15]. Despite these limitations, percutaneous closure in non-surgical candidates has demonstrated symptomatic improvement (NYHA class, echocardiography and haemolysis parameters) in 70-80% of reported cases [2,16].…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, paravalvar leaks result from rupture of one or more sutures securing the prosthesis to the valve annulus, and typically occur during the first post-operative year [2]. Clinical manifestations are a consequence of reduced net cardiac output and/or transfusion-dependent haemolytic anaemia.…”
Section: S Ignificant Paravalvar Regurgitation Around Prostheticmentioning
confidence: 99%
“…More recently, the technique has been described with the off-label use of various existing Amplatzer devices ( fig. 1) for septal occlusion (ASD or muscular VSD) or patent ductus arteriosus closure [10][11][12][13][14][15][16][17]. The oval rather than circular shaped AVP (Amplatzer Vascular Plug) III device (approved in Europe and Canada but not yet in United States for vascular occlusion) has been available since 2008 and has the advantage of being better adapted to close oval or crescent-shaped leaks (the most commonly found shape of PVL).…”
Section: Transcatheter Approach To Pvlmentioning
confidence: 99%